2013
DOI: 10.1155/2013/254017
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment of Nonhealing Venous Leg Ulcer with Propolis Ointment

Abstract: An investigation of effectiveness of topical treatment of nonhealing chronic venous leg ulcers with propolis ointment was conducted. 56 patients were included in the study and randomized into two groups. In group 1, there were 28 patients (ulceration area: 6.9–9.78 cm2) treated by means of topical propolis ointment application and short stretch bandage compression. In group 2, there were 29 patients (ulceration area: 7.2–9.4 cm2) treated by means of Unna boot leg compression without topical propolis treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 12 publications
0
26
0
3
Order By: Relevance
“…2 In the 17th century, Stradivarius used varnish containing propolis on his violins. In dermatology, it has been used, for example, for burns, 26 leg ulcers, 27 psoriasis, 28 atopic dermatitis, recurrent aphthous ulcers, 29 warts, 30 herpes labialis, herpes genitalis, 31 and for wound healing and tissue regeneration. 18 The balsam possesses antibacterial, antifungal, and antiviral properties and may have a wide range of other beneficial biological activities: anti-inflammatory, antioxidant, antiulcerogenic, local anesthetic, hepatoprotective, antitumor (cytotoxic), 19,20 immune-stimulating/ modulatory, 19,21 cariostatic, spasmolytic, and many other biological properties.…”
mentioning
confidence: 99%
“…2 In the 17th century, Stradivarius used varnish containing propolis on his violins. In dermatology, it has been used, for example, for burns, 26 leg ulcers, 27 psoriasis, 28 atopic dermatitis, recurrent aphthous ulcers, 29 warts, 30 herpes labialis, herpes genitalis, 31 and for wound healing and tissue regeneration. 18 The balsam possesses antibacterial, antifungal, and antiviral properties and may have a wide range of other beneficial biological activities: anti-inflammatory, antioxidant, antiulcerogenic, local anesthetic, hepatoprotective, antitumor (cytotoxic), 19,20 immune-stimulating/ modulatory, 19,21 cariostatic, spasmolytic, and many other biological properties.…”
mentioning
confidence: 99%
“…Propolis ointment management was also reported to stimulate the efficacy of the short stretch bandage compression stocking and the combined venous ulcer treatment which was more effective than Unna's boot compression alone [ 14 ]. Pessolato et al reported in their studies that burn treatment with propolis stimulated the process of tissue regeneration and led to inhibition of local inflammation, which indicates that treatment with the mentioned apitherapeutic was successful in the initiation of the burn healing, and accelerated the biosynthesis of collagen fibres (estimated by morphometry) in all the evaluated periods [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The applied propolis ointments at concentrations of 5% and 7% were chosen on the basis of the literature knowledge and experimental studies investigating the anti-inflammatory effect of the topical formulation containing propolis at abovementioned concentrations [ 14 , 15 ]. On the other hand, 5% and 7% propolis ointments are commonly used as topically applied propolis extracts that belong to the natural product available on the polish pharmaceutical market, being also listed in the Journal of Medicinal Products List admitted to trade on Polish territory.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical trials have been conducted to investigate the therapeutic activities of propolis for different skin lesions. 10, 117,118 Gregory et al 10 conducted a clinical study to compare the healing effect of propolis cream and SSD in superficial second-degree burns. Despite the limitations of the study, in particular, the low number of patients, the time between treatments, and the absence of data about bacterial colonization, results show a beneficial effect of propolis, leading to a reduced inflammation and an improved healing process.…”
Section: Animal-derived Productsmentioning
confidence: 99%
“…All ulcers treated with propolis were completely healed after 6 weeks of treatment, while in the control group (treated with compression dressings) the healing time was significantly higher (16 weeks). 117 Evidence suggests a significant increase in the use of propolis in wound care, mainly due to its anti-inflammatory, antioxidant, and healing activities. However, in order to improve the clinical use of propolis, it is necessary to develop novel manufacturing strategies and quality control methods, ensuring an extensive characterization of its chemical constituents and pharmacological properties.…”
Section: Animal-derived Productsmentioning
confidence: 99%